(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article examines the role of Spanish as a professional communication tool for tour guides and as a factor in the development of inbound tourism in the Republic of Uzbekistan. The study analyzes the impact of Spanish proficiency on the quality of tourism services, intercultural interaction, and the professional development of tourism personnel. Particular attention is given to the analytical examination of the Spanish-speaking tourism segment and the prospects for integrating language proficiency into tourism development strategies in Uzbekistan.